Cardiotoxicity with rituximab, cyclophosphamide, non-pegylated liposomal doxorubicin, vincristine and prednisolone compared to rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone in frontline treatment of patients with diffuse large B-cell lymphoma: A randomised phase-III study from the Austrian Cancer Drug Therapy Working Group [Arbeitsgemeinschaft Medikamentöse Tumortherapie AGMT](NHL-14). (May 2016) - Fridrik, Michael A.; Jaeger, Ulrich; Petzer, Andreas; Willenbacher, Wolfgang; Keil, Felix; Lang, Alois; Andel, Johannes; Burgstaller, Sonja; Krieger, Otto; Oberaigner, Willi; Sihorsch, Kurt; Greil, Richard
Abstract: Background: Chemoimmunotherapy containing rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone (R-CHOP) is the standard treatment for diffuse large B-cell lymphoma (DLBCL). Doxorubicin may induce early and late cardiotoxicity. Non-pegylated liposomal (NPL) doxorubicin may reduce cardiotoxicity. Patients and methods: Patients with untreated CD20+ DLBCL were randomised to conventional R-CHOP chemoimmunotherapy or rituximab, cyclophosphamide, non-pegylated liposomal doxorubicin, vincristine and prednisolone (R-COMP) with doxorubicin substituted by NPL-doxorubicin. Left ventricular ejection fraction (LVEF) and N-terminal pro B-type natriuretic peptide (NT-proBNP) levels were measured before each treatment cycle and after the end of treatment. Results: The mean LVEF of 178 and 158 measurements in the R-COMP and R-CHOP arms was 63.31% and 62.25%, respectively ( P  = 0.167). During treatment the LVEF measurements were below 50% in 10/218 (4.6%) in the R-COMP arm and 31/196 (15.8%) in the R-CHOP arm ( P <0.001). Thirty-six of 40 (90%) patients in the R-COMP arm, but only 24/36 (66.7%) in the R-CHOP arm had all NT-proBNP levels below 400 pg/ml during and at the end of treatment ( P  = 0.013). There were more serious adverse events in the R-CHOP arm (26 versus 40, P  = 0.029). Infections were more common (15 versus 28) in the R-CHOP arm. Interpretation: In patients with normal cardiac function, six cycles of R-CHOP resulted in a low rate of early cardiotoxicity. NPL-doxorubicin did not reduce cardiotoxicity, although cardiac safety signals were elevated in R-CHOP compared to R-COMP. Funding: Cephalon provided the Arbeitsgemeinschaft Medikamentöse Tumortherapie with NPL-doxorubicin and an unrestricted grant, but was not involved in the study protocol, data acquisition, data analysis or the writing of the paper. Highlights: Rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone (R-CHOP) results in low rate of acute cardiac toxicity. Rituximab, cyclophosphamide, non-pegylated liposomal doxorubicin, vincristine and prednisolone (R-COMP) did not reduce acute cardiac toxicity. N-terminal pro B-type natriuretic peptide may be an early marker of cardiac toxicity. R-COMP had a lower infection rate compared to R-CHOP.